51. Reference data for quantitative motor unit potential and interference pattern analysis in the genioglossus muscle. Issue 12 (December 2016) - Zardoni, M.; Gianelli, F.; Bruno, S.; Raimondi, E.; Nascimbene, C.; Mariani, C.; Osio, M.
Abstract : Needle electromyography (EMG) of the genioglossus muscle is a useful tool in patients with swallowing problems, that are common in many muscle and nerve diseases. Characteristic changes in motor unit potentials (MUPs) can be distinguished with MUP and interference pattern (IP) analysis. The purpose of this study was to establish reference intervals for MUP parameters using template operated multi-MUP analysis and to evaluate the IP features in the genioglossus muscle (GM) of healthy adults. We studied 28 healthy volunteers (11 men, 17 women, mean age 39 ± 12 years) with standard disposable concentric EMG needles (recording area 0.07 mm2) and an EMG system with standard settings (filters: 5 Hz–10 kHz), using an inframandibular approach. For each MUP parameter (amplitude, duration, turns) mean values and outlier limits (5th and 95th percentile) were calculated from the first 20 sampled MUPs. Data from IP plots (turns/amplitude, activity/envelope and activity/NSS) were collected in order to build normal clouds which contain >90% of the data points. MUP parameters obtained from the GM are similar to those published in literature. IP analysis is not available for healthy GM to our knowledge and could be an objective tool to quantitate the degree of abnormality in muscle and nerve diseases.